EVALUASI KEBIJAKAN TENTANG PENYELENGGARAAN PERHUBUNGAN PADA PELAYANAN ANGKUTAN UMUM PENUMPANG DI KOTA CIMAHI - Zulfikar, Waluyo; Prayoga, Indra Aditya (Program Studi Administrasi Publik, FISIP, Universitas Tulang Bawang Lampung, 2023)
The policy regarding the implementation of transportation in Cimahi City does not specifically regulate passenger public transport services so that it is suspected to be the cause of the poor operation of passenger public transportation in Cimahi City. This study aims to analyze data and information so as to get an overview of policy evaluation regarding the implementation of transportation in Cimahi City with case studies on passenger public transport services. The method used is a case study with a qualitative approach. Data collection techniques used are observation, interviews and documentation studies. Checking the validity of the data is done by triangulation. Data analysis was carried out including the stages of data reduction, data presentation, and conclusions or verification. Based on the research results, a clearer picture is obtained that passenger public transport services in Cimahi City are measured by effectiveness factors based on quality, quantity and time, efficiency of available resources, adequacy of policies in overcoming problems, equity of services and policy benefits, government responsiveness to problems arising from the implementation of policies, and the accuracy of policy targets in achieving policy objectives has not run optimally. Observing the results of the research, it is hoped that policy makers in Cimahi City will be able to review regulations and reformulate more specific policies that specifically address passenger public transport services. In addition, it is recommended to develop a Smart Passenger Public Transport System based on information and communication technology which can be used as an alternative solution. Keywords: Policy Evaluation; Implementation of Transportation; Passenger Public Transport Services